Aroma precursors of cigars from different tobacco parts and origins, and their correlations with sensory characteristics - Geng, Zhaoliang; He, Pei; Gao, Huajun; Liu, Jian; Qiu, Jun; Cai, Bin (Frontiers in Plant Science, 2023)
Cigars are developing rapidly around the world, but the content characteristics of aroma precursors and their contribution to sensory perception have not been fully elucidated. In this study, 69 aroma precursors from 61 tobaccos of different parts and origins were systematically determined, and the sensory characteristics of middle leaves from different origins and their correlation with aroma precursors were evaluated. The results showed that tobacco parts mainly affected amino acid content, and contents of nicotine, oxalic acid, malic acid, isovaleric acid, cystine, glutarnine, glycine, isoleucine, glutamicacid, asparticacid, and fructose-proline were significantly changed. Tobacco origins mainly influenced the contents of amino acids, polyacids and high fatty acids, and sugar alcohols, and significantly affected the contents of myosmine, anabasine, nonanoic acid, propanetriol, mannitol, mannose, glucose, alanine, arginine, glutarnine, glutamicacid, histidine, serine, threonine, tryptophan, fructose-alanine, and fructose-asparagine. The flavor characteristics were prominent by wood aroma, and the style and quality characteristics varied greatly among different origins of middle leaves. There were 34, 21, and 22 aroma precursors with high correlations with flavor, style, and quality characteristics. This study provides support for regulating the content and coordination of aroma precursors in different tobacco parts and origins to improve sensory characteristics.